Littérature et Apartheid: La réception de Lewis Nkosi en France. Issue 1 (2nd January 2016) - Starck-Adler, Astrid
ABSTRACT: Lewis Nkosi had very close ties with France, its literature, thinkers and language. For more than one reason it is worth investigating the reception which his work enjoys in France. It goes back, firstly, to the interests which French Africanists like Jacques Alvarez-Pereire or later Jean Sévry showed for Nkosi as a person and for his writings. Secondly, Nkosi's emblematic and innovative novel Mating Birds, 1986 was instantly translated into French as Le sable des Blancs (Balland 1986), then re-issued as Livre de poche and later on by Dapper with a postscript by the Chadian writer Nimrod (2002). In the French academic world the interest for anglophone literature is a late phenomenon. At the same time there was a will to introduce the anti-apartheid struggle to French intellectuals as well as to a broader audience. As such the reception of Lewis Nkosi's work is part of a wider one on contemporary South African writers whose writings were translated and published in anthologies, scholarly collections on South African literature or Conference proceedings. On the other hand Lewis Nkosi is perceived first of all as a brilliant critic rewarded for his essays (Dakar 1965, Montpellier 1988); paradoxically these have never been translated into French, apart from short excerpts or the address given at the University of Montpellier, "Vu de l'extérieur : La littérature d'Afrique du Sud et la crise des représentations, écrivains noirs, écrivains blancs » (1989). Some of his short stories were, however, published in French: Présence Africaine was the first in 1968 to publish a short story called "Muzi " (1968). Then one has to wait until 1983 to see his short story "Le prisonnier " appearing in French. An excerpt from his play, the third act of Le rythme de violence  (1985) introduced him as a play writer, a brevity compensated partly by the translation of Le psychiatre noir  and its performance at the Pompidou Centre in 2002. In 2010, his novel Mandela et moi was published by Actes Sud and reissued the following year by "Terres solidaires" with a preface by the Ivorian writer Véronique Tadjo. Unfortunately the author who was already very ill couldn't benefit anymore from the recognition he had acquired in France. My paper's aim is to analyse the different perspectives from which Lewis Nkosi's work has been looked at in France. Whereas Lilyan Kesteloot underlines Nkosi's "nationalisme exacerbé" (exacerbated nationalism), Jean Sévry noticed: "Cet homme a été trop negligé: sans doute parce qu'il gêne trop" (This man has been too neglected: probably because he disturbs too much", 1989).